The in vitro Production Potentialities of Secondary Toxic Metabolites by the Fungal Factory Fusarium verticillioides Is, Fortunately, Largely Underestimated in Fields: Pioneering Study on Fumonisins - Dozolme, Pascale Marie Aimée; Moukha, Serge Maria (Frontiers in Microbiology, 2020)
This study presents fungi infrequently viewed as fungal factories for secondary metabolite production resources such as mycotoxins in Ascomycota. Additionally, we demonstrated that biochemical warfare of Fusarium verticillioides factory against animal cells are not only due to mycotoxins such as fumonisins, but acute cytotoxic firing is based on different excreted secondary metabolite series, potentially leading to animal and human diseases. In this study, fumonisins, which can be followed by in situ localization, quantification or expression of the key gene implicated in their synthesis, are used to understand secondary metabolite production by this fungus. It is known that F. verticillioides produces mycotoxins such as fumonisins on cereals; but until now, there is no evidence demonstrating a method to totally block fumonisin production on feed and food. In this paper, we explained, what was never clearly established before, that fumonisin production depends on two bottlenecks. The fumonisin synthesis and secretion in fungal articles of the mycelium are medium-independent and follow the fungal cell cycle developmental program (ontogenesis). Conversely, the fumonisin excretion into the medium depends on its composition, which also impacts fumonisin biosynthesis level. Using a high-pressure-freezing method, we showed that, in non-permissive fumonisin excretion (NPFE) medium, FB1 is sequestered inside extra-vesicles and in the first third of the cell wall next to the plasmalemma, leading to the hypothesis that the fungus develops mechanisms to protect its cytosolic homeostasis against this cytotoxic. In permissive fumonisin excretion (PFE) medium, leading to very high quantities of excreted fumonisins, FB1 localized inside extra-vesicles, crosses the entire cell wall thickness and then releases into the medium. Our results demonstrated a delayed and lower expression of Fvpks-gene in mycelium developed on NPFE-medium as compared to PFE-medium. Conversely, higher amounts of fumonisins were accumulated in NPFE grown mycelium than in PFE grown mycelium. Thus, our results demonstrated for the first time that we have to take in account that the synthesis and secretion inside the article of secondary metabolites depend on the occurrence of cryptic biochemical specialized articles, differentiated in the mycelium. However, those are not morphologically different from other colonial hyphae.